Bioactive Compounds, Ruminal Fermentation, and Anthelmintic Activity of Specialty Coffee and Spent Coffee Grounds In Vitro - Matej Leško; Daniel Petrič; Matúš Várady; Pola Sidoruk; Robert Mikula; Sylwester Ślusarczyk; Paweł Edward Hodurek; Michaela Komáromyová; Michal Babják; Marián Várady; Amlan Kumar Patra; Adam Cieslak; et al. (Agriculture)
We quantified the bioactive compounds of Ethiopian coffee (ETH), spent coffee grounds SCGs from ETH (SCG-ETH), and mixed SCGs (SCG-MIX) prepared by filtration methods and investigated the effect of SCG-ETH on ruminal fermentation as well as the anthelmintic activity of ETH. Three substrates, meadow hay (MH)-barley grain (MH-BG), MH-SCG-ETH, and BG-SCG-ETH (1:1 w/w), were fermented using an in vitro gas production technique. The bioactive compounds were quantitatively analyzed using ultra-high-resolution mass spectrometry. We performed an in vitro larval development test to determine the anthelmintic effect of an aqueous extract of ETH against the gastrointestinal nematode (GIN) Haemonchus contortus. The total content of bioactive compounds was highest in SCG-ETH, followed by SCG-MIX and ETH (35.2, 31.2, and 20.9 mg/g dry matter, respectively). Total gas and methane production (p < 0.001) were decreased by both MH-SCG-ETH and BG-SCG-ETH. The in vitro digestibility of dry matter was higher for MH-SCG-ETH and BG-SCG-ETH than for MH-BG. The aqueous ETH extract exhibited a strong larvicidal effect, with a mean lethal dose of 13.2 mg/mL for 50% mortality and 31.9 mg/L for 99% mortality. SCG substrates have the potential to modulate ruminal fermentation and serve as a source of anthelmintic bioactive compounds against GINs in ruminants.